Crosstalk between efferocytic myeloid cells and T-cells and its relevance to atherosclerosis - Ngai, David; Sukka, Santosh R.; Tabas, Ira (Frontiers in Immunology, 2024)
The interplay between myeloid cells and T-lymphocytes is critical to the regulation of host defense and inflammation resolution. Dysregulation of this interaction can contribute to the development of chronic inflammatory diseases. Important among these diseases is atherosclerosis, which refers to focal lesions in the arterial intima driven by elevated apolipoprotein B-containing lipoproteins, notably low-density lipoprotein (LDL), and characterized by the formation of a plaque composed of inflammatory immune cells, a collection of dead cells and lipids called the necrotic core, and a fibrous cap. As the disease progresses, the necrotic core expands, and the fibrous cap becomes thin, which increases the risk of plaque rupture or erosion. Plaque rupture leads to a rapid thrombotic response that can give rise to heart attack, stroke, or sudden death. With marked lowering of circulating LDL, however, plaques become more stable and cardiac risk is lowered-a process known as atherosclerosis regression. A critical aspect of both atherosclerosis progression and regression is the crosstalk between innate (myeloid cells) and adaptive (Tlymphocytes) immune cells. Myeloid cells are specialized at clearing apoptotic cells by a process called efferocytosis, which is necessary for inflammation resolution. In advanced disease, efferocytosis is impaired, leading to secondary necrosis of apoptotic cells, inflammation, and, most importantly, defective tissue resolution. In regression, efferocytosis is reawakened aiding in inflammation resolution and plaque stabilization. Here, we will explore how efferocytosing myeloid cells could affect T-cell function and vice versa through antigen presentation, secreted factors, and cell-cell contacts and how this cellular crosstalk may contribute to the progression or regression of atherosclerosis.